Percepção e integração dos atores sociais no turismo no espaço rural na serra da mantiqueira: o caso do município de Piranguçu, MG - Souza, João Pedro Machado e (2019)
From the middle of the twentieth century transformations promoted new economic dynamics in rural areas. Tourism in rural area (TRA) emerges as one of the main activities for rural aereas economic revitalization. The rural tourism context in the county of Piranguçu / MG has been gaining importance in recent years. In this context, the objective of this study was to examine the perception of social actors about tourism and their interactions in the development of integrated rural tourism (IRT). In this study was adopted as methodology field research, participant observation and documentary research, focusing on five groups of actors, namely: family farming, local public authority, tour operator, tourist resource provider and institution of organized civil society. The results showed diversity in agricultural production and tourist attractions, mainly natural resources and outdoor activities. There is a possibility of bond between tourism and local agriculture, because the low value and the market shortage were the major problems in the commercialization and the majority of the farmers were favorable to the development of the TRA and interested in participating in the activity, mainly for the potential of economic return. The actors directly linked to TRA also emphasized the economic benefits of tourism. However, the social actors do not present joint strategies to leverage tourism, and the actions of the public power are limited in the sense of uniting these actors and improving the local tourist structure. TRA is not developed to a degree that affects local economic and social dynamics. On the other hand, there is an enormous potential due to the tourist attractions and the relative predisposition of the familiar agriculture actors to become involved with the TRA. The weak actors articulation / participation and the lack of information are the main obstacles to the progress of the TRA. Therefore, IRT is still an abstract reality in the county, recommending a greater articulation of the social actors and greater effort of the local government.